Ludificación didáctica en el aprendizaje de la multiplicación en el quinto grado “A”, de la escuela “Miguel Riofrío” Loja, período 2023-2024 - Córdova Jumbo, Andy José (2024)
This research highlights the innovative application of didactic gamification in solving mathematical problems based on the basic operation of multiplication; the general objective of the study is: To determine the influence of gamification in the teaching of multiplication in the students of fifth grade parallel "A", of the "Miguel Riofrío" school in Loja city, period 2023-2024, which was supported by three specific objectives, the first one consisted in Identifying the strategies that the teacher applies for the teaching-learning of the mathematical operation of multiplication to the students; the second, to design a didactic guide based on playful strategies for the teaching-learning of multiplication, and the third, to evaluate the effectiveness of the playful strategies in the teaching of the mathematical operation of multiplication. On the other hand, the type of research applied was descriptive in nature, likewise a non-experimental research design was used, with a mixed approach to understand and observe the population studied in its natural environment, in the same way the scientific, descriptive, inductive, analytical and statistical methods were used, the techniques used were the interview and the pre- and post-evaluation, in addition, the instruments implemented were the pre- and post-evaluation questionnaire, which contributed effectively to the collection of data. It is essential to emphasize that the playful strategies help significantly in the teaching and learning of multiplication, since they allow achieving an improvement in the academic performance of students, consolidating an interactive and meaningful learning.